Analisis Optimalisasi Sistem Operasional Asuransi Syariah di Indonesia - Zenita Alvina Fauziah; Risma Syan Sabilla; Rifa Khoerunnisa; Joni Joni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Indonesia is currently experiencing rapid and dynamic development, especially in the field of Sharia insurance. Sharia insurance has become an increasingly important and strategic sector in the Indonesian financial industry. This significant development is clearly reflected in data showing notable and consistent growth in the contribution of Sharia insurance to the overall insurance industry in the country. Sharia insurance is an economic activity that aims to help (ta'awun) and share risks (sharing of risk) among fellow participants in a mutually beneficial manner. Optimizing Sharia operational systems is a both a concept and practical approach to managing the operations of financial institutions or businesses based on Islamic or Sharia principles. The research method used in this study is a descriptive method based on a qualitative approach. The type of research undertaken is literature research, conducted by utilizing literature (references). This research aims to identify various challenges faced in Sharia insurance operational systems.